2019
DOI: 10.1007/s10068-019-00596-7
|View full text |Cite
|
Sign up to set email alerts
|

Extraction conditions for Rosa gallica petal extracts with anti-skin aging activities

Abstract: The anti-skin inflammatory activities of rose petal extracts have been described in our previous study. Because skin inflammation is closely linked to skin aging, our study investigated the effects of Rosa gallica petals on skin aging-related activities such as skin whitening and anti-wrinkle properties. Each sample was prepared via extraction using different ethanol ratios with the objective of evaluationg optimal extraction conditions for industrial application. Aqueous 50% (v/v) EtOH extract of R. gallica p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In the current study, RPE was orally administered to mice and its protective effect against skin aging was examined. While a previous study reported the effect of RPE against UVB−induced skin aging under in vitro conditions [ 24 , 37 ], the efficacy of RPE in vivo was unknown. This is the first report to demonstrate that oral administration of Rosa gallica can block UVB−mediated skin aging in vivo without any noticeable toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, RPE was orally administered to mice and its protective effect against skin aging was examined. While a previous study reported the effect of RPE against UVB−induced skin aging under in vitro conditions [ 24 , 37 ], the efficacy of RPE in vivo was unknown. This is the first report to demonstrate that oral administration of Rosa gallica can block UVB−mediated skin aging in vivo without any noticeable toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Rosa gallica is one of the most commonly used Rosa species for cosmetic, medicinal, and culinary purposes [ 22 , 23 ]. Although the potential of the Rosa gallica extract to prevent biomarkers of skin aging in vitro has been reported [ 24 ], there has been no study demonstrating the anti−skin aging effect of Rosa gallica in vivo. Moreover, active ingredients responsible for the bioactivity of Rosa gallica and Rosa species are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins are claimed to suppress natural oxidative process, to protect the body from neurodegenerative and cardiovascular diseases [7] and have antidiabetic effects [8]. Cosmetology studies have confirmed R. x gallica's effects on skin rehydration, minimizing the production of age-related wrinkles, nourishing the epidermis, improving skin elasticity, and having a rejuvenating impact [9].…”
Section: Introductionmentioning
confidence: 99%
“…R. canina hip powder, containing seeds and shells, was recently shown to increase cell longevity, improve skin wrinkles, moisture, and elasticity [ 4 ]. Petal extract of R. gallica decreased the expression of solar UV-induced MMP-1, which is a hallmark of wrinkle formation [ 18 ]. Extracts and compounds isolated from R. canina, R. gallica , and R. rugosa have been extensively studied to assess their efficacy as potential skin-lightening ingredients [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%